Knowledge About Nutritional Intake In Pregnant Women With Anemia - Saepul, Saepul; Hermayanti, Yanti; Platini, Hesti (JURNAL PENDIDIKAN KEPERAWATAN INDONESIA, 2019)
Anemia or a lack of blood cells during pregnancy and childbirth is very dangerous. It may cause pregnant women to be at risk for bleeding during childbirth and hinder infant growth and development.Â This study aims to determine the knowledge of pregnant women with anemia about nutrition during pregnancy. The research design used in this study was quantitative descriptive, with 137 pregnant women with anemia as the population and a total sample of 58 respondents taken with random sampling technique. The variable in this study is the knowledge of pregnant women with anemia about nutritional intake. This study shows that the majority of the pregnant women had poor knowledge (84.48%) of nutritional intake, and only a small number had good knowledge (15.52%).Â With almost all pregnant women with anemia in the study having a lack of knowledge about nutritional intake, there is a concern that the baby will be negatively affected. The implication of the results highlights the important role of health workers to provide information about good nutrition during pregnancy, particularly the impact of tea-drinking habit.